The effects of adjuvant honey therapy on disease activity, lymphocyte function and lymphocyte subsets in patients with systemic lupus erythematosus (SLE) - Daud, Kamaliah Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Objectives: To compare the effects of adjuvant tualang honey therapy versus conventional therapy alone on disease activity, lymphocyte functions and lymphocyte subsets in SLE patients. Methodology: Sixty SLE patients from Hospital Universiti Sains Malaysia were randomized into two equal groups, group 1 receiving conventional treatment with low dose steroid and cyclophosphamide or azathioprim, group 2 receiving same treatment in addition to tualang honey 20 gm twice a day. Disease activity was measured in all patients every 3 months by SLEDAI score, the function of T lymphocyte was determined at baseline and after 6 months by measuring the expression of 3 lymphocyte activation markers (HLADR, CD45RO and CD25). Enumeration of lymphocyte subsets (CD3, CD4, CDB, CD19, and CD16/56) was done at baseline and after 6 months. Results: The SLEDAI score was significantly decreased in honey group compared to non honey group after 3 and 6 months of follow up. There was a significant decrease in the expression of CD8CD45RO and CD8CD25 in honey group.There was a significant increase in CD3 and CD16/56 percentage in honey group after 6 months follow up. Conclusion: The use of honey therapy as adjuvant to conventional treatment in patients with SLE was found to be useful in suppressing disease activity and enhancing lymphocyte function and lymphocyte subsets.